Building the Capacity for Mission through Use of the Principles of Good Practice for Student Affairs at Catholic Colleges and Universities: A Survey of Presidents and Senior Student Affairs Officers - James, Michael J.; Estanek, Sandra M. (Catholic Education: A Journal of Inquiry and Practice, 2012)
Dialogue about Catholic identity has been taking place at American Catholic colleges and universities since the publication of Ex Corde Ecclesiae in 1990. That student affairs professionals do their work within the context of the mission of the university is a concept that has been accepted from the earliest stages of the establishment of student affairs as an independent profession in the beginning of the twentieth century. For the past 20 years, student affairs professionals at Catholic colleges and universities have been building their capacity for mission integration in a variety of professional development seminars and institutes, largely supported by the work of Catholic higher education associations and sponsoring religious communities, with the intention of increasing the presence and integration of the Catholic mission and religious charism at the institutions in which they work. The <a href="http://www.bc.edu/content/bc/schools/lsoe/cce/highered/research/jcr%3acontent/content/download/file.res/Principles%20of%20Good%20Practice%20in%20Student%20Affairs%20at%20Catholic%20Colleges%20and%20Universities.pdf" target="_blank">Principles of Good Practice for Student Affairs at Catholic Colleges and Universities (The Principles) are the latest mission-driven resource to be developed at a national level in support of the continuing efforts by student affairs professionals and others working at Catholic colleges and universities to build capacity for mission-driven work. This article describes the development of The Principles as a mission-centered resource for student affairs professionals at Catholic colleges and universities. This article further presents the findings of a survey of presidents and senior student affairs officers (SSAOs) at Catholic colleges and universities in the United States and Canada regarding how The Principles are being utilized at their institutions to create mission-driven practices in student affairs work and to form mission-knowledgeable student affairs professionals. This article concludes with a discussion about the efficacy of The Principles to be used in continuing efforts across the diversity of institutions that constitute Catholic higher education in productive and meaningful ways to build a culture of mission integrated institutions.